The relationship between self-control and police misconduct: a multi-agency study of first-line police supervisors - Donner, Christopher M. (Criminal justice and behavior, 2016)
Prior research has identified several individual, organizational, and community-level correlates of police misconduct, but studies based on theoretical explanations have only recently emerged in the literature. The purpose of the current study was to examine the potential relationship between self-control and police misconduct using both Gottfredson and Hirschi?s original version of self-control theory and Hirschi?s revised version of the theory. Data from a multi-agency sample of 101 first-line police supervisors demonstrated that self-control, as measured by both conceptualizations of the theory, was significantly related to self-reported prior engagement in police misconduct as well as the likelihood of future misconduct. The results are discussed in terms of theoretical and policy implications, as well as in terms of study limitations and directions for future research.